USE OF PROTECTION SCREEN IN CONVENTIONAL AVIARIES (CALIFORNIAN TYPE) FOR LAYING HENS - Lourençoni,Dian (2019)
ABSTRACT The objective of this work was to evaluate the thermal environment inside conventional cages for laying hens, with and without the use of protective screens. This research was conducted in two conventional cages (open cage), where each cage had half of its area surrounded by high density polyethylene mesh (HDPE) with a diameter of 2.0 cm, and the other half was kept fully open. Hyline W-36 and Dekalb Brown laying hens were housed in these cages. The wind speed, dry bulb temperature (tdb), black globe temperature, humidity index (BGHI), and enthalpy (H) were analyzed. The results indicate that the use of the screen reduced the wind speed inside the cage by 0.22 m s−1. The presence of the screen affected tdb, BGHI, and H in some of the evaluated periods evaluated, making these values higher than those of the treatment without screen. However, the obtained values are within or below the thermal comfort range for laying birds. Therefore, the use of HDPE screen in the cages altered their internal environment. However, it is not enough to hinder the thermal comfort of the housed animals.